Shattering the myth October 20, 1944 - Lazaro, Cheche (Quezon City Probe Productions, 1994)
The 50th anniversary of MacArthur's Leyte landing. Interviews of war veterans on their experiences during the war.
VHS.
Keywords: Philippine Sea, Battles of the, 1944.; Filipino; World War -- Personal narratives. -- 1939-1945.; World War -- Anniversaries, etc. -- 1939-1945 -- Philippines